The Influence of Polyurethane Towards The Mechanical Properties of Stone Mastic Asphalt Mixture - Ahmad, Nuranis Sofia; Masri, Khairil Azman; Md Shahnewaz, Shoaib; Che Puan, Othman; Moon, Juhyuk (International Journal of Integrated Engineering, 2025)
Hot mix asphalt (HMA) with a gap-graded composition is referred to as stone mastic asphalt (SMA). The coarse aggregates are the main component contributing to the stability and strength of SMA mixtures. However, due to the gap-graded nature of SMA, permanent deformation and low tensile strength have become significant concerns in the early deterioration of asphalt and the lifespan of pavements, especially for SMA. The study compares the modified SMA 20 and conventional SMA 20 by conducting laboratory tests and performance assessments. In this investigation, polyurethane (PU) is mixed with heated aggregate, and the polyurethane dosage ranges from 2% to 6%. The tests conducted were the Cantabro test, Marshall stability test, indirect tensile strength (ITS) test, and moisture susceptibility test. The results show significant improvement with the addition of 6% PU.  The 6% PU-SMA is considered to have better abrasion resistance, stability, flow, stiffness, ITS and tensile strength ratio (TSR). The maximum ITS value is 308 kPa (6%) with a TSR value of 89%. The optimal amount of PU required for SMA to achieve both values was 6%, as concluded by all the tests. It can be inferred that the engineering properties of SMA can be improved by the presence of PU when it is concentrated appropriately. Therefore, the effectiveness of the SMA with the PU-modified mixture is also improved, with approximately 20% improvements in abrasion resistance, 45% in stability, and 20% in ITS.